Study on pharmacokinetic interactions between SHR2554 and itraconazole in healthy subjects: A single‐center, open‐label phase I trial - Deng, Kunhong; Zou, Yi; Zou, Chan; Wang, Hong; Xiang, Yuxia; Yang, Xiaoyan; Yang, Shuang; Cui, Chang; Yang, Guoping; Huang, Jie (Cancer medicine (Malden, MA), 2023)
Background SHR2554, a novel oral Enhancer of Zeste Homolog 2 inhibitor, shows broad‐spectrum anti‐tumor efficacy in preclinical studies. As SHR2554 is mainly metabolized by CYP3A4, it is helpful to conduct research on the effects of itraconazole, a strong inhibitor of CYP3A4‐metabolizing enzymes, on the pharmacokinetic characteristics and safety of SHR2554. Methods We conducted a single‐center, open‐label pharmacokinetic study of itraconazole on SHR2554 in 18 healthy Chinese subjects. Subjects were orally administrated SHR2554 50 mg on Day 1, itraconazole 200 mg Quaque Die (QD) from Days 4 to 7, SHR2554 50 mg co‐administrated with itraconazole 200 mg on Day 8, and itraconazole 200 mg QD from Days 9 to 12. Then, 4 ml of venous blood was collected at predetermined time points. Plasma SHR2554 concentrations were analyzed using a validated high‐performance liquid chromatography tandem mass spectrometry method. Pharmacokinetic parameters were calculated using Phoenix WinNonlin v8.1. Results The Cmax of SHR2554 alone and in combination was 10.197 ± 7.0262 ng·ml−1 versus 70.538 ± 25.0219 ng·ml−1, AUC0–∞ was 50.99 ± 19.358 h·ng·ml−1 versus 641.53 ± 319.538 h·ng·ml−1, and AUC0–t was 28.70 ± 18.913 h·ng·ml−1 versus 612.13 ± 315.720 h·ng·ml−1. Co‐administration of SHR2554 and itraconazole caused 7.73‐, 12.47‐, and 23.75‐fold adjusted geometric mean ratios increases in SHR2554 Cmax, AUC0−∞ and AUC0−t respectively. The co‐administration regimen was well tolerated and had a good safety profile. Conclusions Compared with a single dose of SHR2554 50 mg, the exposure of SHR2554 in vivo was significantly affected by the combined administration of itraconazole. Compared with a single dose of SHR2554 50 mg, the exposure of SHR2554 in vivo was significantly elevated by the combined administration of itraconazole. The co‐administration regimen was well tolerated and had a good safety profile.